Developing Grades 1-6 Teachers’ English Communication Skills and English Teaching Techniques Using Training and Coaching in Lop Buri Thailand - Kongsoongnoen, Kanya; Watcharapanyawong, Somchai (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2017)
The purposes of this research were (1) to develop English for communication skills for grades 1-6 teachers, 2) to develop the teachers’ English teaching skills, and (3) to increase the students’ English Achievement. The participants were 15 teachers with no degree in English from 14 small size primary schools in Lop Buri province Thailand. The 30 hour English communication and 30 hour English teaching training were provided to the teachers. School visits with Coaching approach were applied for supporting their teaching at schools as well as teaching materials the teachers needed. A questionnaire comprising both open and closed-ended questions was used to evaluate the teachers’ teaching. The interview questions and the teachers’ reflection form were conducted for collecting their perception on the project, percentage and mean were applied to analyze quantitative data whereas content analysis was conducted for qualitative data.The findings showed that the teachers’ English for communication skills and English teaching skills were increased. The teachers’ English communication skills and their teaching skills were higher than before whereas their teaching application was at a medium level. Fifty percent of the teachers’ teaching skills were at a high level while 20% barely applied their teaching experience they received from the training and coaches. One hundred percent of the teachers agreed that the project was the most useful for them and many highlighted that they’d immensely learned teaching techniques and just realized that they could make their English class interesting for the students because they felt confident after the training. However, a few teachers had no chance to teach English because their schools had someone qualified to teach instead.